An Analysis of the Effects of the Compact City on Economic Activities in Japan - Fumitoshi Mizutani; Noriyoshi Nakayama; Tomoyasu Tanaka (European Regional Science Association (ERSA), 2015)
The main purpose of this paper is to evaluate how the form and urban policies of ga compact cityh affect its economic activities. In general, bigger cities have more advantages such as agglomeration economies, but too-big cities have the disadvantages of external diseconomies such as environmental pollution and traffic congestion. Therefore, governments of industrial countries have an interest in promoting compact cities, but empirical evidence regarding how the formation and policies of compact cities affect economic activities is unclear or undocumented. In order to investigate our research question, we will conduct an empirical analysis using data from Japanese cities. As there is no official definition in Japan, we first define metropolitan areas and create a data set of 269 metropolitan areas in Japan for the year 2000. Then we estimate citiesf urban economic models by using econometric techniques. These urban economic models consist of four sections: 1) a compact city section, 2) a labor section, 3) a production section, and 4) a population section. First, the compact city section shows how the cityfs compactness measure is determined. Second, the labor section shows how the numbers of employees, the share of each industryfs employees, and so on are determined. There are 11 industries defined here, including manufacturing, public utilities, retailers, wholesalers, and so on. Third, by estimating the production function, the production section shows the extent of each industryfs economic activity in a city. The production functions estimated here are for 11 industries. Last, the population section shows how the cityfs population is determined by considering degree of economic activities, amenities, and so on. After we estimate several formulas regarding the above issues, we will conduct simulations in order to evaluate how the degree of a cityfs compactness affects economic activities and number of employees in a city. We are also able to determine what kind of factors affect the degree of a cityfs compactness. These empirical results may also be useful in determining policy aimed a achieving a sustainable city size.
Keywords: R11; R15; 330; Compact City; Urban Economic Model; Economic Activities; Japanese Cities